Peran Majlis Ta’lim Nurul Iman dalam Pembentukan Sikap Keagamaan Masyarakat di Rt 10/02 Kelurahan Pagar Dewa Kec Selebar Bengkulu - Maryam Maryam (Institut Agama Islam Negeri Bengkulu, 2019)
This study aims to examine the role of the majelis ta ‟lim in developing human qualities in society. Taklim Assembly is regulated in Article 26 paragraph 4 of RI Law Number 20 of 2003 concerning the National Education System. This study uses a qualitative approach with triangulation analysis. The results of this study found that the existence of the Ta'lim Assembly in the era of globalization is very important and one of the most important strongholds in counteracting the negative effects of globalization itself. besides that it also functions as a fostering and developing Islamic religion, a park of spiritual recreation, an arena of silaturrahmi, a means of continuous dialogue between ulama, umaroh and the people and as a medium to convey the idea of modernization that is beneficial for the development of the people.